Achieving and control of partial denitrification in anoxic-oxic process of real municipal wastewater treatment plant. (December 2021) - Liu, Xiuhong; Liu, Runyu; Yang, Qing; Cui, Bin; Wu, Wenjun; Zhao, Xiaoyin; Wang, Yaxin
Graphical abstract: Highlights: Partial denitrification was achieved with NAP higher than 90% in MWWTP. Compare to NaAc, GLC promoted high efficient and rapid partial denitrification. Using NaAc, partial denitrification was controlled with no nitrite accumulation. DGAOs and Thaurea were the dominant communities for partial denitrification. Abstract: Partial denitrification is an alternative process to provide stable nitrite for anammox. In this study, based on full-scale and lab-scale experiments, achieving and control of partial denitrification and the microbial mechanism were studied for 17 months in municipal wastewater treatment plant (MWWTP). Using glucose (GLC) as sole carbon source, partial denitrification was successfully achieved with nitrite accumulation percentage (NAP) higher than 90%; whereas, using sodium acetate (NaAc) as sole carbon source, nitrite accumulation was effectively controlled with economic and efficient carbon usage. Candidatus Competibacter and Thaurea were the dominant communities for partial denitrification. Denitrifying glycogen accumulating organisms (DGAOs), Thauera, denitrifying phosphorus accumulating organisms (DPAOs), GAOs, PAOs and denitrifiers coexisted in MWWTP, resulting in COD specific removal rate (CODSRR) of 883.10 ~ 1188.92 mgN/gMLVSS/h during partial denitrification. Through adjustment of Anoxic-Oxic (A/O) operation to anoxic operation, the growth of GAOs and PAOs could be limited.